Deconstruction of AKM Literacy in PAI Lessons on the Learning Performance of MBKM Students: Dekonstruksi AKM Literasi Pada Pelajaran PAI Terhadap Performa Pembelajaran Siswa MBKM - Lismawati, Lismawati; Astutik, Anita Puji; Ramadhan, Alif Rizky; Rahmanto, Muhammad Arifin; Iryanti, Shobah Shofariyani (Universitas Muhammadiyah Sidoarjo, 2023)
The AKM assessment is a major issue undertaken by Education Minister Nadiem Makarim in addressing challenges that arise in national education. The main idea behind this development comes from the poor results of PISA 2018, which has made many experts concerned about the existing results. Therefore, in addressing this issue, Minister of Education Nadiem attempted to create an assessment similar to PISA, which is AKM. In practice, AKM has two branches that are tested with an additional one survey. The AKM assessment is none other than the assessment of literacy and numeracy, as well as a survey of character. In practice, these three tests are an effort to significantly map the abilities of students every year from individual to national level. So that the development of national education can be monitored regularly. One of the assessments that is raised is the assessment of literacy or assessment that emphasizes students' ability to critically analyze text structure. This assessment is tasked with documenting the literacy abilities of students nationally. But in practice, there are still various issues that have not been fully studied regarding the position of the literacy assessment as an agent of change. Therefore, in this research, the researcher tries to study and deconstruct the AKM literacy assessment, as an effort to improve the quality and performance of student independent learning.